Study on the Stress-relieving Effect of Transdermal Drug Delivery System Using Natural Substances - Kyung-Yae Hyun; Gil-Hyun Lee (Journal of experimental & biomedical sciences, 2024)
Objectives: This study was conducted to verify the efficacy of the stress transdermal drug delivery system(patch)developed in the previous study. Methods: A total of 85 people were targeted to confirm the changes in theautonomic nervous system and brain wave index before and after the application of the patch. An electroencephalograph to measure brain wave activity in the frontal lobe and a finger sensor to measure electrocardiogram, heart rate, and arterial oxygen saturation were attached to the patient. After attaching the sensor to a subject who did not have a patch attached, a stabilization period of 5 minutes was allowed and biosignals were collected for approximately 2 minutes. Results: After applying the patch, the stress index was confirmed to decrease by approximately 31.9% ± 4.2% comparedto before the experiment. After applying the patch, the ratio of alpha waves in the brain wave was found to increase by 9.4% ± 5.3% and the heart rate variability index increased from 8.6 ± 1.3 points to 9.3 ± 1.8. Conclusion: Considering these research results, it is thought that the patch used in this study has the efficacy ofstabilizing the autonomic nervous system, and is related to the stabilization of brain function accordingly.